Impact of Non-Pulmonary Vein Foci on the Outcome of the Second Session of Catheter Ablation for Paroxysmal Atrial Fibrillation - TAKIGAWA, MASATERU; TAKAHASHI, ATSUSHI; KUWAHARA, TAISHI; OKUBO, KENJI; TAKAHASHI, YOSHIHIDE; NAKASHIMA, EMIKO; WATARI, YUJI; YAMAO, KAZUYA; NAKAJIMA, JUN; TAKAGI, KATSUMASA; KIMURA, SHIGEKI; HIKITA, HIROYUKI; et al. (Journal of cardiovascular electrophysiology, 2015)
Impact of Non‐PV AF Foci on the Second Catheter Ablation for PAF Background Paroxysmal atrial fibrillation (AF) is primarily triggered by pulmonary veins (PVs). However, non‐PV AF foci may also trigger AF. Methods We examined 207 patients (mean age, 62 ± 11 years; 166 men) who underwent a second catheter ablation (CA) and evaluated the clinical significance of non‐PV AF foci on the outcomes. Results Electrical reconnections between the PVs and left atrium (LA) were observed in 162 patients (78.3%). Non‐PV AF foci were identified in 95 patients (45.9%, 60 patients with successfully ablated non‐PV AF foci and 35 with unmappable non‐PV AF foci). During a median follow‐up period of 22.7 months, 61 patients (29.5%; 18/112 [16.1%] without non‐PV AF foci vs. 20/60 [33.3%] with successfully ablated non‐PV AF foci vs. 23/35 [65.7%] with unmappable non‐PV AF foci, P < 0.0001) developed AF recurrence; 52 (85.2%) developed recurrence within 1 year. The presence of non‐PV AF foci was a significant clinical predictor of AF recurrence after the second CA; successfully ablated non‐PV AF foci increased the AF recurrence risk by 2.24 times (95% confidence interval [CI], 1.12–4.54; P = 0.02), and unmappable AF foci increased this risk by 5.58 times (95% CI, 2.73–11.63; P < 0.0001). Conclusion Nearly half of the patients had non‐PV AF foci at the second CA session. AF recurred after the second CA session in approximately 30%, with most recurrences happening within 1 year. The presence of non‐PV AF foci significantly increased the AF recurrence risk after a second CA. When non‐PV AF foci were unmappable, the AF recurrence rate was extremely high.